1999
DOI: 10.1159/000030439
|View full text |Cite
|
Sign up to set email alerts
|

Multifocality in Renal Cell Carcinoma: A Bilateral Event?

Abstract: Objectives: The major disadvantage of nephron-sparing surgery for renal cell carcinoma is the risk of local recurrence. This is most likely a manifestation of undetected small additional tumors in the renal remnant. To define more clearly the incidence and nature of unilateral and bilateral multifocal tumors, an autopsy study was undertaken. Materials and Methods: In a series of 14,793 autopsies from 1985 to 1995, 260 renal cell carcinomas were found. In all cases of renal cell carcinoma a search for small ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…Multifocality has been associated mainly with papillary subtype [3,5,8,22,23] , clear subtype [12] and mixed histological patterns [3] . Uzzo et al [17] reviewed more than 1,000 cases in the literature from 1980 to 2000 and reported that papillary RCC is associated with a higher incidence of multifocality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multifocality has been associated mainly with papillary subtype [3,5,8,22,23] , clear subtype [12] and mixed histological patterns [3] . Uzzo et al [17] reviewed more than 1,000 cases in the literature from 1980 to 2000 and reported that papillary RCC is associated with a higher incidence of multifocality.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found no such association [1-4, 7, 8, 13-16] . Interestingly, Wunderlich et al [23] reported that tumors with good grading showed a higher incidence of multifocality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…post mortem examinations, Wunderlich et al found 260 renal tumours, 36 of which (18.95%) were multifocal [91]. Applying the findings of molecular genetic tests, papillary tumours are polyclonal, i.e.…”
Section: Studies On the Clonality Of Multiplex Papillary Kidney Tumoursmentioning
confidence: 99%
“…Our studies were carried out about five years before the publication of the comprehensive reviews cited before [86][87][88][89][90][91]. Our intention was to utilise the HC in diagnostic practice, on the basis of the chromosomal disorders described in the publications that laid its foundations, because the chromosomal deviations described by the HC appeared highly coherent and diagnostic [98,99].…”
Section: V/4 Histological and Genetic Classification In The Case Of Pmentioning
confidence: 99%